Synthesis and X-ray characterization of two new 1,4-benzoxazine derivatives: Structural analysis and DFT calculations - Bashir, Muhammad Adnan (2024)
The synthesis and XRD characterization of two new 1,4-benzoxazine derivatives (3a-5a) namely ethyl‐6‐nitro‐3a‐(p‐tolylamino)‐1,2,3,3a‐tetrahydrobenzo[b]cyclopenta[e][1,4]oxa-zine‐9a(9H)‐carboxylate (3a) and methyl-6,10b-dimethyl-5a,6,10b,11-tetrahydrobenzo[5,6][1,4]oxazino[2,3-b]indole-2-carboxylate (5a) are reported herein. In both compounds it is observed the formation of π···π and CH···π interactions and strong NH···O H-bonds, which were studied energetically at the PBE0-D3/def2-TZVP level of theory. The Hisrhfeld surface and QTAIM analyses and NCI plots were used to study the nature and the extent of different intermolecular interactions observed in both structures, revealing the existence of additional and synthons. In addition, using the potential energy density as energy predictor, the QTAIM method is useful to investigate the relative contribution of each interaction to the formation of the assemblies.